Gli anni della cupola 1417-1436 : Archivio digitale delle fonti dell'Opera di Santa Maria del Fiore - Opera di Santa Maria del Fiore (2006)
[Dt.:] Die Volltextdatenbank erschließt sämtliche überlieferten Dokumente, die den Bau der Kuppel des Florentiner Domes von 1417 bis 1436 betreffen. Es kann nach Begriffen, Daten, Textsegmenten, Namen etc. recherchiert werden. Die Navigation sowie die Darstellung der Transkriptionen ist sehr komfortabel. - [Engl.:] The Years of the Cupola is a textual and structured digital archive of the documentary sources of the Opera di Santa Maria del Fiore. The period covered, 1417-1436, corresponds to the two decades during which Brunelleschi s dome was designed and constructed. The project consists of the complete edition of the Opera s sources for the period under consideration, accompanied by a system of structured analysis that presents its contents to the user and provides easy access to them.